Sex Differences in Risk Factors and Natural History of Oral Human Papillomavirus Infection. (10th February 2016) - D'Souza, Gypsyamber; Wentz, Alicia; Kluz, Nicole; Zhang, Yuehan; Sugar, Elizabeth; Youngfellow, Renee M.; Guo, Yingshi; Xiao, Weihong; Gillison, Maura L.
Abstract: Oral human papillomavirus genotype 16 (HPV16) infection causes oropharyngeal squamous cell carcinoma (SCC), and the prevalence of oropharyngeal SCC is higher among men than women in the United States. In a cohort study of oral HPV infection among 409 individuals aged 18–25 years, the risk among men but not among women significantly increased as the number of recent (ie, within the prior 3 months) oral sex partners increased ( P interaction = .05). In contrast, the risk among women but not among men significantly decreased as the lifetime number of vaginal sex partners increased ( P interaction = .037). Men were also significantly less likely than women to clear oral HPV infection. Our data contribute to understanding sex differences in risk for HPV-positive oropharyngeal SCC. Clinical Trials Registration.  NCT00994019.